DIVESTMENT VIEWED FROM THE PERSPECTIVE OF JUSTICE (PT. NNT IN WEST NUSA TENGGARA) - Zainal Asikin (Fakultas Hukum Universitas Mataram, 2013)
The Shares divestment Process of PT NTT becomes interesting legal problem to criticize because the case of shares divestment that involves a big company foreign company in gold mining sector that happened in Indonesia especially in West Nusa Tenggara.The research analyze about how the Indonesian Law regulates on shares divestment and how the divestment practice conducted by Local government of West Nusa Tenggara. Through the normative approach (normative study) and case approach. It was concluded that the law in Indonesian has not been regulated on the process of shares divestment by the Government (Local Company). However through the legal analogy method so the Acts Number 1 Year 2004 on State treasury and some of its implementation regulations applicable to the investments and divestments process. Likewise, as long as the divestment cooperation aims to build the public infrastructure so that the President Regulation Number 65 Year 2005 refers to President Number 13 Year 2010 could be umbrella of law. In the process of shares divestment of PT. NNT, it is found the procedural mistakes by the Government of West Nusa Tenggara, as well as there are collaboration agreement contain a conflict of norm, so that potentially causing losses to the state. Keywords: the Cooperation Agreement, Divestiture Shares